The Effect of Callus and Corns Removal Treatments on Foot Geometry Parameters, Foot Pressure, and Foot Pain Reduction in Women - Antończak, Paweł Piotr; Hartman-Petrycka, Magdalena; Garncarczyk, Agnieszka; Adamczyk, Katarzyna; Wcisło-Dziadecka, Dominika; Błońska-Fajfrowska, Barbara (Applied sciences, 2023)
Foot pain and deformities are significant problems that increase with age and are significantly more prevalent in women. Calluses and corns are both common and inconvenient, and the accompanying pain complaints significantly reduce the quality of life. Professional foot care is one of the key elements in the prevention of foot disorders and improves the comfort of people with such problems. The aim of the present research was to assess the impact of podiatry treatments on the foot conditions, including parameters related to foot geometry, the forefoot pressure on the ground, and the occurrence of pain in women over 50. In each volunteer, history and physical examination were performed and an objective assessment with the use of the digital foot scanner and the baropodometric measurements was performed. The examinations were conducted before the beginning of the procedures and up to a week after each of the three podiatry treatments performed at monthly intervals. Specialist foot care treatments influenced the values of the hallux valgus angle, the varus angle of the fifth toe, and the longitudinal arch. After each treatment, the percentage of feet with normal longitudinal arch was significantly greater than before the treatments. The treatments influenced the value of pressure in the forefoot. The percentage of feet with pain decreased significantly after each treatment. Performed podiatry treatments, consisting of the removal of changes related to keratosis, not only normalized the parameters related to foot geometry and the forefoot pressure on the ground but also reduced foot pain.